Quality Assessment of PBM Protocols for Oral Complications in Head and Neck Cancer Patients: Part 1 - Gobbo, Margherita; Merigo, Elisabetta; Arany, Praveen R.; Bensadoun, René-Jean; Santos-Silva, Alan Roger; Gueiros, Luiz Alcino; Ottaviani, Giulia (Frontiers in Oral Health, 2022)
Background Radiotherapy and chemotherapy are frequently employed in head and neck cancer (HNC) patients causing significant side effects that impair life quality and prognosis. Photobiomodulation (PBM) has become a growing approach to managing such oral complications. Despite its proven efficacy and absence of contraindications, there is still a lack of universally accepted disease-specific PBM protocols. Objective A narrative review was conducted to identify the current proposals relating to the use of PBM to treat complications of oncological treatments in HNC patients. Methods An electronic search in PubMed and Scopus databases was performed with the following keywords: (“photobiomodulation” OR “PBM” OR “laser therapy” OR “LLLT” OR “laser”) AND (“head and neck cancer” OR “oral cancer”) AND (“mucositis” OR “oral mucositis” OR “dysgeusia” OR “oedema” OR “xerostomia” OR “dermatitis” OR “trismus”) until October 2021. Results A total of 35 papers were included in the narrative review. Oral mucositis was the most studied complication, and advisable protocols are conceivable. Although there is a growing interest in PBM to manage of xerostomia, radiodermatitis, pain, and trismus, literature is still scarce to propose a universally feasible protocol. Conclusions PBM therapy could significantly prevent or reduce the severity of many side effects related to cancer therapies. More research is needed to obtain recommendations over the preferable parameters.